Functional polymorphisms : bovine calpastatin gene and meat tenderness - Abd Manap, Mohd Nazmi (2012)
Calpastatin is widely known as an endogenous specific inhibitor to the ubiquitously expressed calpain an enzyme responsible for proteolysis of myofibrillar proteins during post-mortem degradation of muscle. The presence of the calpastatin polypeptide in muscle indicates that the activity of calpain can be potentially down regulated which could result in meat toughness. Asssement of calpastatin activity in meat could be a predictive marker to meat tenderness and variation in the gene has the potential to become a candidate genetic marker which is associated with meat tenderness. The variability and inconsistency produced in meat tenderness post-mortem could be reduced if animals could be selected based on this potential genetic marker prior to slaughter which in turn will reduce the cost in meat processing and ultimately achieve the main objective of producing consistently tender meat.